The Sri Lankan Civil War and Australia's Migration Policy Response: A Historical Case Study with Contemporary Implications. Issue 2 (May 2017) - Betts, Judith; Higgins, Claire
Abstract: Sri Lanka's civil war lasted almost 26 years and cost tens of thousands of lives. Since the end of the war in 2009, several thousand asylum seekers from Sri Lanka have sought protection in Australia, but both Labor and Liberal/National Coalition governments have taken a restrictive approach to their arrival and have expressed support for the Sri Lankan government. This article explores Australia's response to the protection needs of Sri Lankans during an earlier era, at the outbreak of the war in 1983, when a Labor government processed Tamils 'in‐country' under Australia's Special Humanitarian Program.